2018
DOI: 10.1016/j.brs.2018.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial direct current brain stimulation decreases impulsivity in ADHD

Abstract: Background Impulsivity is a core deficit in attention deficit hyperactivity disorder (ADHD). Transcranial direct current stimulation (tDCS) of the dorsolateral prefrontal cortex (DLPFC) has been shown to modulate cognitive control circuits and could enhance DLPFC activity, leading to improved impulse control in ADHD. Objective/Hypothesis We predicted 2.0 mA anodal stimulation (tDCS) versus sham stimulation applied over the left DLPFC would improve Conners Continuous Performance Task (CPT) scores. Our seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 95 publications
(131 reference statements)
3
87
0
1
Order By: Relevance
“…In total, 11 separate experiments from 10 studies published from 2014—April 2018 were included in this meta-analysis. In 8 of 10 studies (or 9 of 11 experiments), effects of tDCS on inhibitory control was investigated [6, 6874] and in 5 of 10 studies (or 6 of 11 experiments), tDCS effects on WM were explored [6, 69, 7476]. In what follows, we describe the effect size obtained from studies to examine the efficacy of tDCS in ADHD major neuropsychological symptoms (Please see Fig 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 11 separate experiments from 10 studies published from 2014—April 2018 were included in this meta-analysis. In 8 of 10 studies (or 9 of 11 experiments), effects of tDCS on inhibitory control was investigated [6, 6874] and in 5 of 10 studies (or 6 of 11 experiments), tDCS effects on WM were explored [6, 69, 7476]. In what follows, we describe the effect size obtained from studies to examine the efficacy of tDCS in ADHD major neuropsychological symptoms (Please see Fig 2).…”
Section: Resultsmentioning
confidence: 99%
“…This was supported by the findings from two studies conducted on adult ADHD. The study with 2 mA intensity reported significant improvement in inhibitory control performance [68] while the study with 1 mA intensity reported no significant effects on Go/No-Go task performance [71] despite the fact both studies targeted left dlPFC with anodal tDCS. Stimulation intensity has, therefore, an impact on the effectiveness of tDCS, which is not necessarily linear [99] and should be considered in clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Alpha oscillations following stimulus onset have been increased after multichannel stimulation depending on initially baseline performance. Stimulation-induced changes of alpha oscillations during this nontarget task suggests a transfer effect of the stimulation to functions that have not been entrained during stimulation (Allenby et al, 2018 ). The increase in alpha following stimulus onset could reflect increased response inhibition through the inhibition of related cortical areas (Klimesch, 1996 ; Schmiedt-Fehr et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the lack of significant changes in the SSRT suggests no effects on reactive inhibition. Although there have been positive results in tDCS studies using the SST in a healthy population targeting other areas like the right inferior frontal gyrus [37][38][39][40][41][42] , previous tDCS studies with ADHD patients using the SST and targeting the DLPFC have also found a lack of significant effects on the SSRT and accuracy 28,43 . These results support the formulation of inhibitory control and impulsivity as complex multimodal processes with subdomain specificity (e.g.…”
Section: Flanker Taskmentioning
confidence: 99%